Diagnostic Accuracy of Placenta Accreta Spectrum Scoring System (Pass Scoring) on MRI For Antenatal Diagnosis of Placenta Accreta Spectrum - Jabeen, Sheeza; Khan, Nasir; Majeed, Ahmad; Butt, Nazish; Mumtaz, Saneela; Zahoor, Anam (Biological and Clinical Sciences Research Journal, 2025)
To decrease the chances of misdiagnosis of the placenta accreta spectrum, a scoring method must be developed based on the MRI features and the clinical presentation of patients. Objective: To determine the diagnostic accuracy of PAS-system on MRI to diagnose the placenta accreta spectrum, considering per operative findings after cesarean section as gold standard Study design: It was a cross sectional validation study Methods: The study was executed from Dec 2022 to Jun 2023 at Department of Radiology, Holy Family Hospital, Rawalpindi. Pregnant females of 2nd or 3rd trimester, aged 20-45 years, suspected for placenta accreta spectrum based on ultrasound, or those at high-risk for placenta accreta spectrum were included. Magnetic resonance imaging scan was conducted for all enrolled participants on a 1.5T scanner (Model MRI 450w optima). The MRI findings were then matched with the final diagnosis made based on the operative findings during cesarean section for all the patients. The diagnostic accuracy was evaluated in terms of sensitivity and specificity. Results: There were 95 participants whose mean age was 30.59±3.7 years, with an age range of 21-40 years. Around 50 (52.6%) belonged to the age group of 20 to 30. A sensitivity of 88.0%, specificity of 91.1%, positive predictive value of 91.6%, negative predictive value of 87.2% and diagnostic accuracy of 89.4% was reported. Conclusion: The PAS scoring system based on MRI for PAS is a highly sensitive and accurate imaging modality.